2010
DOI: 10.1002/acr.20174
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of hyaluronate injections in patients with chronic painful shoulder: A meta‐analysis of randomized controlled trials

Abstract: Objective. To elucidate the therapeutic efficacy and safety of injection of hyaluronate (HA) for chronic painful shoulder. Methods. The meta-analysis comprised randomized controlled trials (RCTs) that compared the efficacy of HA injections with that of a placebo. Articles were retrieved through systematic searches of databases, including Medline, EMBase, and Japana Centra Revuo Medicina. The outcome end points were classified into 5 categories: pain, shoulder range of motion (ROM), total functional score, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
1
25
0
4
Order By: Relevance
“…The review concluded that sodium hyaluronate injection was modestly more effective than steroid injection for function and there was an improvement in pain and function compared with placebo. 116 …”
Section: Comparison With Other Effectiveness Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The review concluded that sodium hyaluronate injection was modestly more effective than steroid injection for function and there was an improvement in pain and function compared with placebo. 116 …”
Section: Comparison With Other Effectiveness Researchmentioning
confidence: 99%
“…We are aware of three systematic reviews that have been published since our assessment started: one of corticosteroid injections compared with physiotherapy for frozen shoulder; 115 one of sodium hyaluronate injection for chronic painful shoulder; 116 and one of conservative and surgical interventions for frozen shoulder. 117 A guideline based on a systematic review has also recently been published focusing on diagnosis, assessment and physiotherapy management of frozen shoulder.…”
Section: Comparison With Other Effectiveness Researchmentioning
confidence: 99%
“…In the shoulder joint, recent studies reported good clinical outcomes of an intra-articular or subacromial hyaluronic acid injection for various painful shoulder diseases. 1,6,8,10,11,[19][20][21] Shibata et al 21 described the clinical outcome of an intraarticular hyaluronate injection for 78 shoulders with a rotator cuff tear. They reported that the effective rates in the hyaluronate and steroid groups were 39.5% and 35%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Problem of pain assessment widely discussed in abdominal surgery, traumatology, orthopedics etc [1][2][3][4][5]. Recently this point calls for consideration in otolaryngology, particularly in nasal cavity surgery [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%